Zero outage : putting ICT quality first in the digital era - Kasulke, Stephan; Bensch, Jasmin (Springer International Publishing, 2017)
This reference book shows how the Zero Outage method leads to more stability in operations, more reliability in projects and, ultimately, to greater customer satisfaction. It explains why clear standards for platforms, processes and personnel are essential for ensuring high ICT quality from end to end and what to look out for during changes -- the most common cause of IT outages. Readers also learn how to resolve errors as quickly as possible and permanently eliminate them, and why industry-wide collaboration will only be possible with a shared standard of quality. This book is a practical introduction to making your ICT world even more failsafe and efficient. The authors share key knowledge in quality management and offer an exclusive insight into their extensively tested and continually enhanced formula for success: the Zero Outage approach. Contents · Operational quality: Zero Outage in change, incident and problem management · The Zero Outage Quality Roadmap: Identifying and proactively managing outage risks · Quality in projects: Pain points, early warning systems, de-escalation · Compliance and security: Mastering legal requirements · From customer perception to customer satisfaction · End-to-end quality can be achieved only in collaboration with partners and suppliers · "Zero error" attitude: Entrenching Zero Outage in the corporate culture With a foreword by Dr. Ferri Abolhassan, Director of Telekom Deutschland GmbH. He has been an initiator of Zero Outage. The Authors Stephan Kasulke has been Senior Vice President Quality at T-Systems since 2012. In this role, he manages the worldwide Zero Outage program, which brings improvements to the quality of operations and projects. Jasmin Bensch is Executive Consultant ITIL and Head of Line Office Quality at T-Systems. She has many years of experience in process design and in the optimization of IT outsourcing processes.
Keywords: Information resources management.; Management information systems.; Electric power failures.; elektronické knihy; electronic books